'Everyone thinks that I just need to know a few words and sing some songs to teach English to the kids': primary school English language teachers struggled for their professional legitimacy. Issue 2 (15th March 2019) - Nguyen, Chinh Duc
ABSTRACT: Language teachers' struggles for professional legitimacy have emerged as an area of interest in the field of language teaching research. Grounded in Wenger's concept of 'trajectories of learning', the current study explored the fight for legitimate status of two primary school English language teachers in Vietnam. Data for this article were collected through life-history interviews in which the two participating teachers were encouraged to tell stories about the early days of their teaching careers. The findings of the study reveal that the participants struggled for professional legitimacy during the early stage of their teaching careers. Beyond the school setting, the two teachers encountered negative attitudes towards their teaching profession as teaching languages to young learners was not highly valued in society. Based on the findings, the study pointed to the issue of power relations which, although regarded as a barrier to teachers' professional legitimacy, is not adequately addressed in the concept of 'trajectories of learning'. The study also revealed some implications for legitimising language teachers' professional status.